The teaching techniques and student’s motivation in the english learning on the students of the 8th years of basic education at instituto superior tecnologico Beatriz Cueva de Ayora of Loja city period 2012-2013 - Astudillo Tinoco, Santiago Leonardo (2014)
The present research work entitled: “THE TEACHING TECHNIQUES AND STUDENT’S MOTIVATION IN THE ENGLISH LEARNING ON THE STUDENTS OF THE 8TH YEARS OF BASIC EDUCATION AT INSTITUTO SUPERIOR TECNOLOGICO BEATRIZ CUEVA DE AYORA OF LOJA CITY PERIOD 2012-2013”; has been developed to evaluate if the teaching techniques that teachers apply, affect on the student’s motivation in the English Language Learning process. It was used the scientific method to obtain information about the teaching techniques and if these will help in the teaching-learning process on students, and also were used the analytical and descriptive methods to analyse the surveys applied to students and teachers. The technique applied was the survey to know teachers and students opinion. With the sample of 109 students and 5 English teachers who participated in the surveys. The results of the surveys determined that the teaching techniques applied by teachers influence on the student’s motivation in the process of learning English.